Clinical and epidemiological factors related to mortality due to septic shock in a pediatric intensive care unit - Ricardo Rodriguez-Portilla; Herminio R. Hernández-Díaz (Permanyer, 2024)
Introduction: Septic shock is a potentially life-threatening condition. The aim of this study was to identify clinical and epidemiological factors associated with mortality in pediatric patients admitted to a pediatric intensive care unit (PICU) with septic shock. Materials and methods: A retrospective comparative case series study was conducted with children aged 1 month to 14 years with septic shock from 2018 to 2020 in a PICU in Lima, Peru. Patients were divided into deceased and survivor groups based on their condition at discharge from the PICU. The influence of each variable on mortality was assessed using a logistic regression model. Results: A total of 174 patients were included in the study, with 51 (29.3%) fatalities. Deceased patients, compared to survivors, were older, had a higher incidence of oncological disease (31.4% vs. 14.6%; p = 0.011), more frequently presented with hemoglobin ≤ 9 g/dL (44% vs. 28%; p = 0.043), lactate > 2 mmol/L (70% vs. 44%; p = 0.002), platelets ≤ 150 (×103)/μL (77% vs. 42%; p < 0.001), and pH ≤ 7.1 (31% vs. 6%; p < 0.001). In the logistic regression model, factors related to mortality were having a pH ≤ 7.1 (odds ratio [OR] = 8.95; 95% confidence interval [CI]: 2.52-31.75) and platelets ≤ 150 (×103)/μL (OR = 3.89; 95% CI: 1.40-10.84). Conclusions: Factors associated with mortality in pediatric patients with septic shock were a pH ≤ 7.1 and platelets ≤ 150 (×103)/μL in the assessments conducted upon admission to the PICU.